Prolonged use of oral contraceptive pill, a co-factor for the development of cervical cancer (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This study was carried out to assess the use of oral contraceptive pill as a co-factor for the development of cervical cancer. Among the 100 participants, 71% used oral contraceptives pill. Maximum (40%) used oral contraceptive pill for >5 years whereas 31% for